The Novel Inducer of Innate Immunity HO53 Stimulates Autophagy in Human Airway Epithelial Cells - Myszor Iwona T; Sigurdsson Snaevar; Viktorsdottir Alexia Ros; Agerberth Birgitta; Eskelinen Eeva-Liisa; Ogmundsdottir Margret Helga; Gudmundsson Gudmundur H (KARGER, 2025)
Aroylated phenylenediamines (APDs) are novel modulators of innate immunity with respect to enhancing the expression of antimicrobial peptides and maintaining epithelial barrier integrity. Here, we present a new study on induction of autophagy in human lung epithelial cells by the APD HO53. Interestingly, HO53 affected autophagy in a dose-dependent manner, demonstrated by increased microtubule-associated proteins 1A/1B light-chain 3B (LC3B) processing in mature polarized bronchial epithelial cells. The quantification of LC3B puncta showed increased autophagy flux and formation of autophagosomes visualized by transmission electron microscopy. The phenotypic changes indicated that autophagy induction was associated with activation of 5 ' adenosine monophosphate-activated protein kinase (AMPK), nuclear translocation of transcription factor EB (TFEB), and changes in expression of autophagy-related genes. The kinetics of the explored signaling pathways indicated on activation of AMPK followed by the nuclear translocation of TFEB. Moreover, our data suggest that HO53 modulates epigenetic changes related to induction of autophagy manifested by transcriptional regulation of histone-modifying enzymes. These changes were reflected by decreased ubiquitination of histone 2B at the lysine 120 residue that is associated with autophagy induction. Taken together, HO53 modulates autophagy, a part of the host defense system, through a complex mechanism involving several pathways and epigenetic events.